Comparative Diagnostic Concordance of Low‐cost Endoscopic Remote Consultation Versus Standard Otolaryngology Evaluation - Manuela Restrepo Peláez; Paola Herrera Noreña; Tania Margarita Salgado Gómez; Ingri Julieth Patiño Ariza; Carlos Stiven Zúñiga Bravo; Sebastián Orozco Arteaga (OTO Open)
Abstract Objective To analyze the diagnostic concordance between findings obtained using a low‐cost endoscope during telepresence evaluations and those obtained through conventional otolaryngology consultations. Study Design An observational cross‐sectional study was conducted between September 2022 and October 2023. Setting Second‐level clinic providing in‐person otolaryngology consultations for patients aged 18 and older. Methods A total of 223 evaluations were performed on 217 adult patients, comparing in‐person assessments with remote evaluations using a low‐cost otoendoscopic device. Diagnostic concordance was assessed for 7 otolaryngological conditions: tympanic perforation, myringosclerosis, signs of external otitis, middle ear effusion, turbinate hypertrophy, septal deviation, and tonsillar hypertrophy. Statistical analysis included the calculation of Cohen's κ coefficient and diagnostic performance measures. Results The endoscopic evaluation demonstrated high diagnostic concordance for ear and oral cavity assessments, particularly for tympanic perforation and signs of external otitis (κ of 1 and 0.93, respectively). Conversely, low concordance was observed for nasal findings such as turbinate hypertrophy and septal deviation (κ of 0.07 and 0.11, respectively). Limitations in image resolution and data capture of the low‐cost device were identified. Conclusion The low‐cost endoscope used in telepresence otolaryngology consultations is effective for evaluating ear and oral cavity findings but shows limitations in nasal cavity assessments. Telemedicine in otolaryngology can reduce health care access barriers in settings with limited availability of specialized services. This study underscores the need for continued research and development of more precise diagnostic devices in otolaryngology.